2003
DOI: 10.1046/j.0905-7161.2003.00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of monocortical bone blocks grafted in the human maxilla: a histological and histomorphometric study

Abstract: Local bone defects in the anterior maxilla are commonly grafted with monocortical blocks of autologous bone in order to restore the defect site prior to the placement of dental implants. Increasing evidence suggests that osteocytes are involved in the control of bone remodelling and thus may be important for optimalisation of bone structure around implants, and thus for implant osseointegration. However, it is not well known whether osteocytes will survive when bone blocks are grafted into defects. We grafted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
90
4
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 28 publications
11
90
4
2
Order By: Relevance
“…31,40,41 Zerbo et al performed sinus augmentation surgery using monocortical blocks of autologous chin bone to allow dental implant placement. 19 As a result from biopsies taken at 2.5 and 7 months, the amount of nonvital bone decreased significantly with the time of healing, as it was progressively remodeled into new bone. 19 Zijderveld et al observed predominantly lamellar bone after a healing period of 6 months.…”
Section: Klijn Et Almentioning
confidence: 99%
See 4 more Smart Citations
“…31,40,41 Zerbo et al performed sinus augmentation surgery using monocortical blocks of autologous chin bone to allow dental implant placement. 19 As a result from biopsies taken at 2.5 and 7 months, the amount of nonvital bone decreased significantly with the time of healing, as it was progressively remodeled into new bone. 19 Zijderveld et al observed predominantly lamellar bone after a healing period of 6 months.…”
Section: Klijn Et Almentioning
confidence: 99%
“…19 As a result from biopsies taken at 2.5 and 7 months, the amount of nonvital bone decreased significantly with the time of healing, as it was progressively remodeled into new bone. 19 Zijderveld et al observed predominantly lamellar bone after a healing period of 6 months. 33 Lorenzetti et al performed unilateral augmentation with bone blocks or particulated bone originating from the chin.…”
Section: Klijn Et Almentioning
confidence: 99%
See 3 more Smart Citations